1998
DOI: 10.1007/s003300050442
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal stress fractures of the tibia: comparative study of CT and MR imaging

Abstract: The aim of this study was to compare the performance of CT and MRI in the diagnosis of longitudinal stress fracture of the tibia (LSFT). A retrospective study of imaging findings was performed in 15 patients with LSFT. The CT and MR images were compared for detection of fracture line, callus, bone marrow edema, and soft tissues changes. The CT and MRI techniques allowed the detection of the fracture line in 82 and 73 % of cases, respectively. The callus was always visualized with CT or MRI. The MRI technique h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 11 publications
0
37
0
Order By: Relevance
“…Insufficiency fractures should show no cortical destruction, the presence of which suggests malignancy. 5 …”
Section: Pelvic Insufficiency Fracturementioning
confidence: 99%
“…Insufficiency fractures should show no cortical destruction, the presence of which suggests malignancy. 5 …”
Section: Pelvic Insufficiency Fracturementioning
confidence: 99%
“…On the other hand, even when MTSS is associated with microfractures, it is likely that they will never be large enough to be visible on plane radiography. More recently, CT and MRI have been used to classify both SFs (Bergman and Fredericson, 1999;Deutsch et al, 1997;Feydy et al, 1998;Matin, 1988;Reeder et. al., 1996) and MTSS (Matin, 1988;Deutsch et al, 1997;Beck, 1998;Bergman and Fredericson, 1999).…”
Section: Stage Of Injurymentioning
confidence: 99%
“…al., 1996) and MTSS (Matin, 1988;Deutsch et al, 1997;Beck, 1998;Bergman and Fredericson, 1999). The main advantage of CT is that it provides a good delineation of fine bone detail (Feydy et al, 1998) so both SFs and partial SFs can be more easily observed. Unlike X-ray scans, crosssectional images are possible using CT as this imaging modality uses a large number of Xray beams to reconstruct a slice of bone.…”
Section: Stage Of Injurymentioning
confidence: 99%
“…Longitudinal stress fractures have been reported exclusively in the lower limb. There are several reports of longitudinal stress fractures in the tibia [4,8,10,11] and a small number of reported cases in the femur [22,23]. The diagnosis is important, as some of the imaging features can overlap with inflammatory and neoplastic entities and therefore awareness of the diagnosis and its specific imaging signs is needed.…”
Section: Introductionmentioning
confidence: 98%